Introduction to New Governance and the Business Organization Special Issue of Law and Policy - Condon, Mary (2011)
The point of departure for this exciting collection of articles is to advance the scholarly treatment of “new governance” by shifting its focus away from what regulators do or how they do it, and towards examining the encounter between new governance and business organizations, within those organizations themselves. As is evident from this issue, this shift still provides a broad canvas on which to work, as the types of business activity examined here through the lens of new governance encompass railways, food safety, corporate privacy, and bank lending, as well as securities and derivatives trading. A particular strength of the articles in this issue is the presentation of original empirical research, ranging from surveys of business in the UK food sector (Hutter) and a case study of corporate restructuring (Sarra) to interviews with privacy officers (Bamberger and Mulligan), bankers (Conley and Williams), and corporate monitors (Ford and Hess). While most of the papers focus on specific domestic contexts for business activity, Conley and Williams’ paper is pitched at the global take up of the Equator Principles for project lending, and Ford and Hess comment on comparisons between Canada and the United States in the implementation of corporate monitorship programmes